Nutrigenetics - Dolores Corella (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Precision Medicine, understood as "the emerging approach for disease treatment and prevention that takes into account individual variability in genes, environment, and lifestyle for each person" is currently one of the most talked about themes in biomedicine and great efforts are being made internationally to turn this concept into a reality. As the concept of Precision Medicine spreads, so too does that of "Precision Nutrition", which would have to take individual variability into account when recommending personalized diets. Although huge progress has been made over recent years in research into the genotype in inter-individual responses to diet, proving that this heterogeneity does indeed exist, we still do not have top level scientific evidence to make the eagerly-awaited personalized dietary recommendations, either from the prevention or treatment of different diseases point of view. It is, therefore, essential to gather more information from studies which, from the nutrigenetic point of view, analyze gene-diet interactions in the different intermediate and final phenotypes of diseases. The ideal situation would be to have results available from randomized and controlled clinical trials. Results on gene-diet interactions obtained from large cohorts, and other types of studies with replication in independent samples, are also of great importance. Similarly, if nutrigenetic findings are accompanied by more mechanistic evidence, integrating other omics, this would be of particular interest. Lastly, another topic of interest is to share strategies for implementing genome-based nutritional interventions. Therefore, this Special Issue of Nutrients, "Nutrigenetics", will focus on providing evidence of the inter-individual genetic effects of diet in determining diseases phenotypes. We are looking forward to receiving many submissions from outstanding experts on these topics. Experimental papers, meta-analyses, up-to-date review articles, and commentaries are all welcome.